Cost-Effectiveness of Test-and-Treat Strategies to Reduce the Antibiotic Prescription Rate for Acute Febrile Illness in Primary Healthcare Clinics in Africa - van Dorst, PWM; van der Pol, S; Olliaro, P; Dittrich, S; Nkeramahame, J; Postma, MJ; Boersma, C; van Asselt, ADI (Springer, 2024)
Background: Inappropriate antibiotic use increases selective pressure, contributing to antimicrobial resistance. Point-of-care rapid diagnostic tests (RDTs) would be instrumental to better target antibiotic prescriptions, but widespread implementation of diagnostics for improved management of febrile illnesses is limited. Objective: Our study aims to contribute to evidence-based guidance to inform policymakers on investment decisions regarding interventions that foster more appropriate antibiotic prescriptions, as well as to address the evidence gap on the potential clinical and economic impact of RDTs on antibiotic prescription. Methods: A country-based cost-effectiveness model was developed for Burkina Faso, Ghana and Uganda. The decision tree model simulated seven test strategies for patients with febrile illness to assess the effect of different RDT combinations on antibiotic prescription rate (APR), costs and clinical outcomes. The incremental cost-effectiveness ratio (ICER) was expressed as the incremental cost per percentage point (ppt) reduction in APR. Results: For Burkina Faso and Uganda, testing all patients with a malaria RDT was dominant compared to standard-of-care (SoC) (which included malaria testing). Expanding the test panel with a C-reactive protein (CRP) test resulted in an ICER of $ 0.03 and $ 0.08 per ppt reduction in APR for Burkina Faso and Uganda, respectively. For Ghana, the pairwise comparison with SoC—including malaria and complete blood count testing—indicates that both testing with malaria RDT only and malaria RDT + CRP are dominant. Conclusion: The use of RDTs for patients with febrile illness could effectively reduce APR at minimal additional costs, provided diagnostic algorithms are adhered to. Complementing SoC with CRP testing may increase clinicians’ confidence in prescribing decisions and is a favourable strategy.